After Cloture: Vote Switching, Credit Claiming, and Position Taking in the United States Senate. Issue 1 (2nd January 2018) - Odom, Brett N.; Norris, Justin J.; Meyer, Chase B.
ABSTRACT: Vote switching in the United States Senate is not an uncommon occurrence. Nearly one in 10 cloture-final passage vote pairs involves senators switching their vote. We find that this inconsistency in voting behavior is a result of the combination of electoral pressures and the impact of the traceability of consequences in light of party forces and personal preferences. In general, we find that electorally vulnerable members of the majority party are more likely to engage in vote switching. The same is true of more electorally secure members of the minority party. However, the traceability of consequences is also a governing force in that electorally vulnerable members of the majority party are more likely to use vote switching as a credit claiming opportunity during periods of low media scrutiny. Electorally vulnerable members of the minority party are more likely to engage in position taking when there is greater media scrutiny.